Dinamika Politik Islam dalam Sistem Demokrasi Indonesia - Refra, Mohamad Saleh; Kelibay, Ismed; Widodo, Suranto Eko; Boinauw, Irwan; Rahakbauw, Rahma (Universitas Muhammadiyah Sorong, 2025)
This study examines the dynamics of Islamic politics within Indonesia’s democratic system, a country with a Muslim-majority population that consistently upholds democratic principles. The research aims to understand the direction of Islamic political transformation amid the challenges of modernity, pluralism, and contemporary political rationality. Grounded in Oliver Roy’s theory of Islamic political pragmatism, this study assumes that the failure of political Islam to confront modern realities does not signify the collapse of its ideology, but rather reflects a process of adaptation toward a more pragmatic and contextual form. This research employs a qualitative method with a library research approach, analyzing academic literature such as journal articles relevant to the topic. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that Islamic politics in Indonesia has undergone a pragmatization process, characterized by inclusive, adaptive, and issue-based strategic orientations focusing on universal values such as social justice, democracy, and welfare. This approach sustains the relevance of Islamic politics in a multicultural society. Consequently, understanding the transformation of Islamic politics is crucial for formulating inclusive and democratic public policies that can accommodate religious aspirations without provoking identity polarization, thereby strengthening substantive democracy in Indonesia.